Keanekaragaman Jenis Anura Daerah Cagar Alam Lembah Anai Kabupaten Tanah Datar Sumatera Barat - Mahesa Rafi; Fitra Arya Dwi Nugraha (Jurnal Serambi Biologi, 2022)
Sumatra has a variety of habitats ranging from lowlands with swamps and peatlands to highlands such as tropical rain forests, so that the organisms in it are diverse. However, the actual level of biodiversity is still not well documented. This is due to the weakness and lack of comprehensive field survey efforts. One group of animals that has received less attention is the anura group. Anura surveys have been widely carried out on the island of Sumatra, starting around 50-60 years ago, but the surveys conducted have not been broad or comprehensive, inconsistent or only done sporadically. This study aims to determine the types of anura found in watersheds in the Anai Valley Nature Reserve, Tanah Datar Regency, West Sumatra. Data collection was carried out using the path transect method along the river flow and carried out at night. Found 7 species of anura consisting of 5 families. The value of species richness in the Anai Valley CA watershed is relatively low, namely 1.5855; the value of medium species diversity is 1.4376; and the dominant value is 0.3197.